URGENSI KEMAMPUAN MATEMATIS DALAM MENGANALISIS TEORI-TEORI EKONOMI - Hamni Fadlilah Nasution (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Mathematics can be applied in many fields of study, one of them inEconomics. Many problems in economics can be explained by means ofmathematics both in numbers, and formulas so it can be measuredproperly. If we understand about mathematic and can think somethinghow to solve problem with mathematic, so we have mathematical ability.Mathematical ability is the ability to think in accordance with theprocedures of mathematics. Mathematical ability is used to analyze theexisting problems in the economy. Mathematical abilities includemathematical reasoning, mathematical communication, mathematicalproblem solving, mathematical reasoning, creative thinking and criticalthinking. Therefore, mathematical ability has significant role inEconomics.